1997
DOI: 10.1159/000262377
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Brushite, Monetite and Whitlockite during Equilibration of Human Enamel with Acid Solutions at37C

Abstract: The residues of 5 samples of powdered human enamel, each subjected to 5 sequential equilibrations at 37°C with either 17 or 4 mmol/l phosphoric acid, were examined microscopically. With 17 mmol/l acid, both brushite and monetite were found after 1 equilibration but, after further equilibrations, brushite was no longer present and the abundance of monetite crystals increased. Formation of monetite probably contributed to the lower metastability of this system compared to similar low-pH systems at 25 °C, where m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…Although there is still considerable debate in the literature, brushite (or dicalcium phosphate dihydrate -CaHPO 4 ! 2H 2 O) [Moreno and Zahradnik, 1974], mo netite (CaHPO 4 ) [Featherstone et al, 1978] and Mg-substituted whitlockite [WHM -Ca 9 Mg(HPO 4 )(PO 4 ) 6 ] [Shellis et al, 1997] have all been reported. This is not surprising, as brushite and monetite are more stable than HA under acidic conditions [Brown, 1973]; whereas the mineral phase associated with Mg in (sound) enamel was proposed to be WHM [Driessens and Verbeeck, 1982].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is still considerable debate in the literature, brushite (or dicalcium phosphate dihydrate -CaHPO 4 ! 2H 2 O) [Moreno and Zahradnik, 1974], mo netite (CaHPO 4 ) [Featherstone et al, 1978] and Mg-substituted whitlockite [WHM -Ca 9 Mg(HPO 4 )(PO 4 ) 6 ] [Shellis et al, 1997] have all been reported. This is not surprising, as brushite and monetite are more stable than HA under acidic conditions [Brown, 1973]; whereas the mineral phase associated with Mg in (sound) enamel was proposed to be WHM [Driessens and Verbeeck, 1982].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the saturation status of each solution, pI for a given solid was compared with the negative logarithm of the relevant solubility product (pK). The following pK values were used: octacalcium phosphate (OCP), Ca 4 H(PO 4 ) 4 ·2H 2 O, 48.7 [28]; brushite (BR), CaHPO 4 ·2H 2 O, 6.64 [29]; magnesium whitlockite (MWH), Ca 9 Mg(HPO 4 )(PO 4 ) 6 , 104.4 [30,31]; fluorapatite (FA), Ca 5 (PO 4 ) 3 F, 60.5 [7]; dolomite, CaMgCO 3 , 17.47 [32].…”
Section: Calculationsmentioning
confidence: 99%
“…In experiments 3 and 4, the magnesium-containing solutions with pI HA ^ 58.6 had pI values for magnesium whitlockite of 99.44-103.21 and so would be supersaturated with respect to this solid according to the data of Verbeeck and de Bruyne [1989] and Shellis et al [1997].…”
Section: Resultsmentioning
confidence: 99%